History of establishment and development of Ukrainian legislation in the field of archaeological and cultural heritage - Базелюк, В. В. (Theory and practice of jurisprudence, 2016)
In the article the author has examined questions about the history of the formation and development of Ukrainian legislation in the field of archaeological and cultural heritage.